ON HOBBES’ ARISTOTELITY - Thorp, John (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2020)
In Chapter xlvi of Leviathan Hobbes launches a blistering attack on the curriculum of his own university studies; the gist of this attack is that instead of teaching philosophy the universities teach ‘Aristotelity,’ a slavish adherence to the doctrines of Aristotle. In this paper I ask whether ‘Aristotelity,’ as recounted by Hobbes, is a faithful rendition of the actual teachings of Aristotle. I consider three of Hobbes’ complaints: i) the idea that Aristotle did not acknowledge the priority of mathematics in science; ii) the idea that Aristotle understood essences to be ghostly entities floating around in space separate from the things of which they were the essences; and iii) the idea that Aristotle thought eternity to be a kind of timeless present. In none of these cases is Aristotelity faithful to Aristotle.